USO DO BRINQUEDO NO ATENDIMENTO FISIOTERAPÊUTICO DE CRIANÇAS COM PARALISIA CEREBRAL - Branco, Danyel Pinheiro Castelo (2009)
The cerebral palsy, non progressive disease, undertakes the movements and posture. The current physiotherapy backs to a holistic treatment. To play provides neuropsychomotor development. This study has as objectives investigate the opinion of physiotherapists that act in neuropediactrics about the use of toy in your clinical practice and check your possible use in inventions with children with cerebral palsy. Initially is used the questionnaire of opinion with fifty physiotherapists of various clinical of The Child with Disability Support Association, AACD, checking the use of toys in relation to various physiotherapeutic goals; below, makes observation of sixty consultations, in aquatic and on land physiotherapy, in cerebral palsy, checking the use of each category of toy used on the therapeutic goal. Data obtained in the questionnaire shows; in descending order, the use of: toys sensory-motor 57,7%, to gain the balance (E); 22,2% for motor coordination; 18,5% for postural acquisition (AP) and 2% for muscle relaxation (RM). For make-belie games: 37% (E); 39% (AP); and 24% (CM). For games of rules: 54% (E); 35% (CM); 11% (AP). With assembly games: 25% (CM); 24% (E); 24% (AP). The data of observation revealed that the main therapeutic goals target with the use of toys were: elongation, first 10 ; muscle strengthening; balance and gait training of 10 to 40 ;. As the observed modality of toy there were a predominance of the make-believe at the beginning and in the end of the section and the other categories in the meddle, interspersed way. The data of observation coincided with the questionnaire revealing the systematic use of toys with physiotherapeutic goals.(AU)